Comparison of dried full-fat corn germ and tallow in finishing feedlot diets for heifers - M.J. Sulpizio; T.J. Kessen; E.R. Loe; Sean P. Montgomery; J.N. Pike; J.J. Sindt; R.T. Ethington; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2003)
A trial was conducted using 588 finishing beef heifers (705 lb initially) to compare tallow and dried full-fat corn germ as supplemental energy sources. Pens of 20 to 50 heifers were fed finishing diets containing 1) tallow or 2) corn germ. The tallow diet contained (dry basis) 46% steam-flaked corn, 35% wet corn gluten feed, 3% alfalfa hay, 1.5% soybean meal, and 4% tallow. The corn germ diet contained 41% steam-flaked corn, 35% wet corn gluten feed, 3% alfalfa hay, and 10% corn germ. Diets provided 300 mg monensin, 90 mg tylosin, and 0.5 mg MGA per heifer daily and were fed ad libitum once daily for 110 days. Gains of 2.99 lb/day for tallow and 2.95 lb/day for corn germ were not different (P>0.30), but dry matter intake tended to be greater for cattle fed corn germ than for those fed tallow (P=0.10; 16.7 vs 16.4 lb/day, respectively). Consequently, cattle fed germ were 3.4% less efficient than cattle fed tallow (P<0.04). Hot carcass weight was not different (P>0.40) between treatments. Cattle fed corn germ had more carcasses grading prime (P=0.03), more carcasses grading average choice or higher (P<0.05), and tended to have more marbling (P=0.08) than cattle fed tallow. Incidence of liver abscesses was higher (P<0.02) for cattle fed corn germ than for those fed tallow (4.8% vs 1.8%, respectively). These results indicate that corn germ is a suitable substitute for tallow in finishing rations.
Keywords: Cattlemen& #x27; s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Dried full-fat corn germ; Tallow; Finishing diets; Heifers